COMPARISON ANALYSIS OF PERCEIVED VALUE ON PRICE AND QUALITY BETWEEN MALE AND FEMALE AT HARDCORE FITNESS CENTER - Rambi, Bryan Heintje; Massie, James D.D.; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Increasing in individual income makes peope more care about their health. There are various way that can be done to get it. Changes of the lifestyle as time goes by, make the fitness center become one of many others options that is chosen by both men and women in order to get the healthy body. Remembering about the number of fitness center, then both of quality and price become the things that are always considered as a reference to choose which fitness center that will be taken or used. Manado become one of many cities that is â€infectedâ€ this lifestyle.This research is conducted in Hardcore Gym, one of the famous fitness center in Manado, using quantitative method of independent sampele t-test on 50 customers (25 men and 25 women) that aims to find out is there a significant in customer perceived value based on perceived price and also perceived quality between male and female because of the importance of those two things, price and quality. Several data analysis is used to analyze the problem. This study evaluated the type of comparative research that aims to determine the relationship between two or more variable. In the end the result of this reaserch show that the mean of pricing perspective of female better than men.Â Keywords: perceived value, perceived quality, perceived price